Projeto ótimo de gerador síncrono com enrolamento de campo para microgeração eólica - Carvalho, Joel Ferrari (2021)
The advancement of renewable power generation technologies is in a growing movement, especially wind power – which achieved the highest investment among them in 2020. This paper talks about the design of both the size defining model and the optimum model of a winded rotor synchronous machine; more specifically it talks about the design of a salient pole, low powered wind turbine. Assumptions are made to make the math feasible for the first analytical iteration. Drawing and calculation softwares are used to help the development of this paper. Later on, EFCAD is used to simulate the generator, which gives results on voltage waves, magnetic induction, inductances amongst others. Then a procedure called skewing takes place on the second iteration to lower the voltage harmonics, and the same development process done on the first iteration is done on this second one. This process is repeated on the last iteration, the optimum generator, obtained through CADES through a code written by the author which includes all the necessary equations for optimization. Results show a progressive improvement on some of the main parameters of the machine. Lastly the three iterations are put against each other for comparison's sake and some possible improvements are suggested for some next work.